2001
DOI: 10.1007/s003840100359
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-sensing receptor A986S polymorphism in human rectal cancer

Abstract: Our observation raises the possibility that genetic alterations of CaSR influence the pathogenesis of rectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
23
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 22 publications
4
23
0
Order By: Relevance
“…Accordingly, these data support the hypothesis that the CaSR gene A986S variant might have a role in pathogenesis of CRC. Studies of the effect of CaSR gene A986S variant on colorectal, colon, or rectal cancer have been inconclusive (Speer et al, 2002;Fuszek et al, 2004;Bacsi et al, 2008;Dong et al, 2008;Jenab et al, 2009). Consistent with our findings, most previous studies found no association between this variant and CRC.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Accordingly, these data support the hypothesis that the CaSR gene A986S variant might have a role in pathogenesis of CRC. Studies of the effect of CaSR gene A986S variant on colorectal, colon, or rectal cancer have been inconclusive (Speer et al, 2002;Fuszek et al, 2004;Bacsi et al, 2008;Dong et al, 2008;Jenab et al, 2009). Consistent with our findings, most previous studies found no association between this variant and CRC.…”
Section: Discussionsupporting
confidence: 88%
“…We did not observe significant associations for the A986S variant in the overall analysis and in the analyses stratified by tumor site, sex, or BMI. In work by Speer et al (2002), the authors reported that there was no association between the A986S variant and rectal cancer risk in a population including 56 cases with rectal cancer and 112 controls. However, they found an association between the variant and more advanced rectal tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The promoter region of the CASR gene contains a vitamin D response element, suggesting a potential regulation by vitamin D (44). CASR polymorphisms have been shown to be associated with the risk of colorectal adenomas (26) and increasing stage of rectal cancer (45). However, findings were overall null in a recent comprehensive study of various CASR polymorphisms and haplotypes and the risk of colon cancer (46).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the CaR, apart from its pivotal role in systemic calcium homeostasis, is now being considered as a possible key regulator of cell proliferation, differentiation and chemotaxis (Brown, 2000;Chattopadhyay, 2000). Moreover, its deregulation is causally linked to colon cancer (Speer et al, 2002). Given the complexity of the AT phenotype, it is not surprising that a number of investigations have been undertaken to explore a possible functional link between ATM and calcium signaling.…”
mentioning
confidence: 99%